EVALUASI KINERJA USAHA TERNAK LEBAH MADU DALAM MENDUKUNG PENGELOLAAN HUTAN LESTARI - Yazid, Muhammad; Saputra, Johan; Aryani, Desi (AGROTEKSOS, 2024)
Honey bee farming has a strategic role in supporting sustainable forest management through improving farmers' welfare and environmental conservation. This study aims to evaluate the performance of the honey bee farming business run by the Wana Lestari Forest Farmer Group (KTH) in the working area of KPH Bukit Cogong Lakitan, Musi Rawas Regency. The evaluation was conducted based on economic, ecological, and socio-cultural dimensions using the Best Worst Method (BWM) and VIKOR. The results showed that the economic dimension had the highest score (3.58), indicating that the business provides meaningful economic benefits to farmers. However, the ecological dimension had the lowest score (2.5), indicating that the business is not optimal in supporting environmental conservation. The socio-cultural dimension scored 3.25, indicating that the business has a positive social impact on the surrounding community. The main factors hindering the ecological contribution are the lack of flowering vegetation as a source of bee fodder and the low awareness of farmers towards environmental conservation. Therefore, the recommended strategies to improve the performance of this business are reforestation with flowering vegetation, increased conservation education for farmers, and strengthening the institutionalization of honey bee farmer groups. The results of this study are expected to serve as a basis for formulating more sustainable beekeeping-based forest management policies.